Analisis dan Perancangan Sistem Informasi Pemerintahan Desa Berbasis Web Pada Desa Pelawan Jaya Kabupaten Sarolangun - Firmansyah, Azi; Dodo Zaenal Abidin; Nurhadi (LPPM Universitas Dinamika Bangsa, 2024)
The information system needed by the village community is obtained through messages delivered by the head of the hamlet and the head of the RT in their respective areas which can be conveyed in the forum of routine activities in the community, while the problems that occur in the population administration in the form of additions, changes to family cards and the making of birth certificates, the community must take care of their own population records to the Dukcapil Office in Sarolangun district with a distance traveled which is quite far, namely a trip ± 30 Km round trip, in addition to the absence of a village information system, the village government does not have population archives, both population statistics and aid data statistics. In the research carried out modeling using UML (Unified Modeling Language), in this stage we create a model of information system needs using use case diagrams, activity diagrams, and class diagrams and build prototypes. The purpose of this study is to analyze and design a prototype of a web-based government information system in Pelawan Jaya Village, Sarolangun Regency. The results of the design of this web-based Village Government information system are expected to help the performance of the Village Government in managing the information needed by the community, and the Village Government has digital-based population data, so that at any time it needs population statistics already in this web-based Village Government information system. In addition, with the existence of this Village Government information system, it is hoped that the Village Government will also be transparent and accountable in managing village finances so that the community can know the activities that are being carried out by the Village Government both in terms of development, coaching and community empowerment.